Urinary estrogen metabolites and gastric cancer risk among postmenopausal women. Issue 7 (11th November 2021) - Camargo, M. Constanza; Song, Minkyo; Xu, Xia; Zhao, Isaac; Sampson, Joshua N.; Etemadi, Arash; Brenner, Hermann; Lee, Hwi‐Won; Trabert, Britton; Holleczek, Bernd; Schöttker, Ben; Spaid, Kathleen; et al.
Abstract: Background: The overall incidence of gastric cancer in women is half that in men for most global populations. Sex hormone pathways may be involved in carcinogenesis and estrogens have been postulated to protect women against gastric cancer. Aim: To evaluate associations of gastric cancer with estrogen metabolites in postmenopausal women. Methods and results: We performed an analysis of 233 gastric cancer cases and 281 age‐matched controls from three prospective cohorts and two case‐control studies of early‐stage gastric cancer, mainly conducted in high‐risk Asian populations. Fifteen estrogen‐parent (estrone and estradiol) and ‐metabolite analytes (2‐hydroxyestrone, 2‐hydroxyestradiol, 2‐hydroxyestrone‐3‐methyl ether, 4‐hydroxyestrone; 4‐methoxyestrone, 4‐methoxyestradiol, 2‐methoxyestrone, 2‐methoxyestradiol, estriol, 16α‐hydroxyestrone, 16‐ketoestradiol, 16‐epiestriol, and 17‐epiestriol) were measured in spot urines using liquid chromatography–tandem mass spectrometry. Odds ratios for association with each marker were estimated by logistic regression. Heterogeneity was assessed by Cochran's Q test. Study‐specific odds ratios were pooled by fixed‐effects meta‐analysis. Urinary levels of estrogen‐related molecules were not associated with gastric cancer (adjusted odds ratios ranged from 0.87 to 1.27; p ‐values >.05), with low between‐study heterogeneity ( p ‐values >.1) for all but two metabolites (2‐hydroxyestrone‐3‐methyl ether and 2‐methoxyestradiol). Conclusion: To date, this is the first comprehensive assessment of endogenous estrogens with gastric cancer risk in women. Estrogens do not appear to have an etiologic role in gastric cancer risk among postmenopausal women. Given the complex network of sex steroid hormones and their extreme variation over the lifespan, further evaluation of this hypothesis is warranted.